Estudos das tradições caipiras em Itapetininga - Cardoso, Cristina de Lima (2016)
This research aims to analyze the ways of being, acting and thinking of the heirs of traditions hillbillies that live in the rural area of Itapetininga, a municipality located in the southwest of the State of São Paulo. The contact with these guys, the story of stories, religious practices and to music party, own this every day, manifested individually and collectively, discussed in interviews and analysis of literary productions of authors from the region, show the continuities and changes in hillbillies traditions that are in constant interaction with the manners and customs of the city. Thus, wrapped in the process of "cultural hybridity", remains represented the rustic legacy. The city arouses the interest of man from the countryside, he inhabits and interacts both in the field and in the city, assimilates traditions, fits but does not despise the origins of the field, the ways of the site and the peculiar taste for things of nature